Relação entre leitura de palavras isoladas, consciência fonológica e funções executivas - Dias, Émille Burity (2016)
The Present Work is sectioned into two studies. Study 1. General Objective: To analyze the relationship: Phonological awareness, Executive functions and reading in children 5-8 years; one and in groups Not Readers and Readers; Method: In this study 41 children of both sexes with Middle Ages of 6.44 years. It is 53.7% male and 46.3% female. As children Were Also distributed groups: 1. Readers (48.8%); and Group 2. Do not readers (51.2%). Were used the following instruments: Trails test, digit span, Cancellation for attention test, consciousness proof phonological, reading words and pseudo words (LPI) and reading letters. Main results: the working memory correlates with inhibitory control skills, segmentation, rhyme and reading letters, while cognitive flexibility correlates with reading letters and Reading Words irreguläres. Study 2. General Objective: to seek evidence of psychometric predictors of Reading Skills Test - THPL not respect your regulation. Method: in this study participated 403 children between 4 and 8 years of age (Middle Ages 6.18) of both sexes in public schools and private, pre school students with 3 years. Used was the reading of the predictive skills test - THPL. Main results: performance progression para skill as tasks. As 3rd year children present best skills and tasks nas reaction times. concerning the ability of these children it is noticed that there performance differences between evidence the 2nd year and 3rd school year, confirming this way the effectiveness do THPL To evaluate Children Only Pre-School Children As Also located in the 1st year.